1988
DOI: 10.1029/ja093ia07p07441
|View full text |Cite
|
Sign up to set email alerts
|

Determination of auroral electrostatic potentials using high‐ and low‐altitude particle distributions

Abstract: The Dynamics Explorer (DE) pair of spacecraft provide a unique opportunity to search for the presence of electric fields aligned parallel to magnetic field lines by sampling, nearly simultaneously, the velocity‐space distribution functions of ions and electrons at two points on auroral field lines: DE 1 at high altitudes (9000–15,000 km in this study) and DE 2 at low altitudes (400–800 km). Three independent techniques are used to infer the auroral electrostatic potential difference from the particle distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(132 citation statements)
references
References 42 publications
12
120
0
Order By: Relevance
“…This can be seen in [Reiff et al, 1986[Reiff et al, , 1988[Reiff et al, , 1993. Our simulation results show that inflowing ion beams from the magnetotail can generate potential drops of up to 2.7 kV over an altitude range of a few thousand kilometers (see Figure 5).…”
Section: Formation Of a Parallel Potential Dropmentioning
confidence: 53%
See 1 more Smart Citation
“…This can be seen in [Reiff et al, 1986[Reiff et al, , 1988[Reiff et al, , 1993. Our simulation results show that inflowing ion beams from the magnetotail can generate potential drops of up to 2.7 kV over an altitude range of a few thousand kilometers (see Figure 5).…”
Section: Formation Of a Parallel Potential Dropmentioning
confidence: 53%
“…Observations have indicated, however, that microscale wave-particle interactions play an active role in dissipating and transferring energy in the auroral zone from beam kinetic energy to thermal energy via plasma waves [Reiff et al, 1986[Reiff et al, , 1988 The study here examines both the formation of semiglobal quasi-static parallel electric fields and microscale wave particle interactions in a self-consistent particle-in-cell simulation. This approach differs from static equilibria models constructed for adiabatic conditions [Chiu and Cornwall, 1980;Lyons, 1981;Newman et al, 1986;Cornwall, 1990], kinetic Alfv6n wave models [Lysak and Dum, 1983;Lysak, 1985Lysak, , 1993Kletzing, 1994] [Yamamoto and Kan, 1985], and the investigation of anisotropic magnetotail distributions as a driver for auroral processes [Winglee et al, 1988].…”
mentioning
confidence: 99%
“…Subsequent missions verified this finding. The results from the Dynamics Explorer (DE) mission suggested that there were possibly two acceleration layers [Reiff et al, 1988 and references therein; Gurgiolo and Burch, 1988]. FAST observations also suggest both highand low-altitude acceleration regions ].…”
Section: And References Therein]mentioning
confidence: 99%
“…The results indicate that ions are not only accelerated by the potential, but they are also heated. Mass-dependent heating has been observed previously (Collin, 1987;Reiff et al, 1988;Möbius et al, 1998;Cui et al, 2010), but the details of how such a heating mechanism works still remains unknown. Note that for the O + we observed, there are counts in channels in the adjacent bins relative to the magnetic field direction and the temperature calculation includes their contribution.…”
Section: Observationsmentioning
confidence: 93%